"Reforming Emergency Care": the ambulance impact. A personal view. Issue 2 (26th February 2004) - Robertson-Steel, I
Abstract : "Reforming Emergency Care" has huge implications for ambulance services to develop their future role and the opportunity to improve patient care. This article aims to stimulate debate on the effect on ambulance services in the United Kingdom.